2018
DOI: 10.1021/acs.est.7b05847
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Persulfate by Nanosized Zero-Valent Iron (NZVI): Mechanisms and Transformation Products of NZVI

Abstract: The mechanisms involved in the activation of persulfate by nanosized zero-valent iron (NZVI) were elucidated and the NZVI transformation products identified. Two distinct reaction stages, in terms of the kinetics and radical formation mechanism, were found when phenol was oxidized by the persulfate/NZVI system. In the initial stage, lasting 10 min, Fe was consumed rapidly and sulfate radicals were produced through activation by aqueous Fe. The second stage was governed by Fe catalyzed activation in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(78 citation statements)
references
References 42 publications
1
71
0
Order By: Relevance
“…The lower degradation efficiency in the latter stage of reaction suggests a declined PS activation efficiency, which could be attributed to the loss of Mn component and depletion of Fe 2+ species that was transformed into Fe 3+ [4,25]. Another work concludes that the transformation between Fe 2+ to Fe 3+ and Fe 3+ to Fe 2+ could slowly activate PS (Equation (5)) and would show a slow pollutant degradation stage after the quick degradation stage [26]. Moreover, as suggested in FTIR analysis, functional groups may also contribute to the PS activation reaction.…”
Section: Activation Mechanismmentioning
confidence: 99%
“…The lower degradation efficiency in the latter stage of reaction suggests a declined PS activation efficiency, which could be attributed to the loss of Mn component and depletion of Fe 2+ species that was transformed into Fe 3+ [4,25]. Another work concludes that the transformation between Fe 2+ to Fe 3+ and Fe 3+ to Fe 2+ could slowly activate PS (Equation (5)) and would show a slow pollutant degradation stage after the quick degradation stage [26]. Moreover, as suggested in FTIR analysis, functional groups may also contribute to the PS activation reaction.…”
Section: Activation Mechanismmentioning
confidence: 99%
“…There are a series of available methods for PS activation [25]. It is worth mentioning that nanoscale zero-valent iron (nZVI) activation has attracted increasing attention due to its combined effects of Fe 0 , Fe 2+ , Fe 3+ , FeOOH, and Fe3O4 [26]. Furthermore, nZVI has been verified to be capable for decomposing organic pollutants through the reaction with dissolved oxygen to generate • OH, O2 • , and HO2 • [27,28].…”
Section: Methodsmentioning
confidence: 99%
“…It was found that Fe(II)/sulfite system can achieve good oxidation of all SAs by means of FeSO3 + species (Reactions (5), (6), and (28)) ( Table S2, Exp. 39, 48, and 57), since Fe(II) could be easily oxidized to Fe(III) in the presence of O2 (Reaction (5) and (35)).…”
Section: Sulfonamide Degradation By the Fe(ii)/sulfite Systemmentioning
confidence: 99%
“…Fe 2+ → Fe 3+ + e - (35) On the other hand, in the presence of an excess of sulfite, the rapid formation of Fe(III) is followed by a slower redox process, during which Fe(II) oxidation is independent of its concentration [40]. SO3 •− radicals, which could be produced by Fe(II) and Fe(III) reaction with sulfite (Reactions (4)-(28)), should then raise the sulfonamide degradation.…”
Section: Sulfonamide Degradation By the Fe(ii)/sulfite Systemmentioning
confidence: 99%
See 1 more Smart Citation